1990
DOI: 10.2307/2048277
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative Functions on Arithmetic Progressions

Abstract: Abstract.Let / be a multiplicative arithmetic function satisfying \f\ < 1 , let x > 10 and 2 < Q < x1/3 . It is shown that, with suitable integers q\>2 and qi > 2 , the estimate n=a mod q {n,q)=\ holds uniformly for (a,q) = 1 and all moduli q < Q that are not multiples of Q\ or q2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Elliott [4,5] showed that this is ≪ x(log log x/ log x) 1 8 for all q except possibly for multiples of a certain exceptional modulus r: note that this is non-trivial in the range q ≤ (log x) 1 8 +o(1) . Hildebrand [14] showed that (1.7) is ≪ x/(q √ log A) for all q ≤ Q except possibly for multiples of one of at most two exceptional moduli r and r ′ . Our result improves both of these, by understanding the asymptotics in all cases, at worst in terms of the exceptional moduli.…”
Section: More Precise Resultsmentioning
confidence: 99%
“…Elliott [4,5] showed that this is ≪ x(log log x/ log x) 1 8 for all q except possibly for multiples of a certain exceptional modulus r: note that this is non-trivial in the range q ≤ (log x) 1 8 +o(1) . Hildebrand [14] showed that (1.7) is ≪ x/(q √ log A) for all q ≤ Q except possibly for multiples of one of at most two exceptional moduli r and r ′ . Our result improves both of these, by understanding the asymptotics in all cases, at worst in terms of the exceptional moduli.…”
Section: More Precise Resultsmentioning
confidence: 99%